2020
DOI: 10.1155/2020/1678780
|View full text |Cite
|
Sign up to set email alerts
|

Detection of CD39 and a Highly Glycosylated Isoform of Soluble CD73 in the Plasma of Patients with Cervical Cancer: Correlation with Disease Progression

Abstract: Persistent infection with high-risk human papillomavirus (HR-HPV) is the main factor in the development of cervical cancer (CC). The presence of immunosuppressive factors plays an important role in the development of this type of cancer. To determine whether CD39 and CD73, which participate in the production of immunosuppressive adenosine (Ado), are involved in the progression of CC, we compared the concentrations and hydrolytic activity of these ectonucleotidases in platelet-free plasma (PFP) samples between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Tumor cells can overexpress CD39 compared with normal cells; however, elevated levels have been also reported in endothelial cells, cancer-associated fibroblasts (CAF) and several immune subpopulations, particularly, natural killer (NK) cells, tumor-associated-macrophages (TAM) and tumor-infiltrating lymphocytes (TILs) including Tregs and CD8 + T cells [ 23 , 24 , 25 , 26 , 27 , 28 ]. High CD39 expression is considered a marker of poor outcome and disease progression [ 29 , 30 , 31 ].…”
Section: Adenosine Pathway and Cd39/cd73 Expression In The Tumor Microenvironmentmentioning
confidence: 99%
“…Tumor cells can overexpress CD39 compared with normal cells; however, elevated levels have been also reported in endothelial cells, cancer-associated fibroblasts (CAF) and several immune subpopulations, particularly, natural killer (NK) cells, tumor-associated-macrophages (TAM) and tumor-infiltrating lymphocytes (TILs) including Tregs and CD8 + T cells [ 23 , 24 , 25 , 26 , 27 , 28 ]. High CD39 expression is considered a marker of poor outcome and disease progression [ 29 , 30 , 31 ].…”
Section: Adenosine Pathway and Cd39/cd73 Expression In The Tumor Microenvironmentmentioning
confidence: 99%
“…ENTPDase and CD73 are required to maintain the stability of the tumor environment by hydrolyzing ATP and AMP. The critical roles of ENTPDase and CD73 in tumors have been confirmed in many studies [ 34–36 ]. For instance, the plasma concentrations and activity of CD39 (ENTPD1) in patients with cervical cancer play an important role in the progression of tumors and may be valuable markers.…”
Section: Discussionmentioning
confidence: 88%
“…According to previous study, the circulating level of sCD73 is a predictor for the development and severity of acute pancreatitis (7). Studies showed CD73 promoted the proliferation and migration of breast cancer cells, hepatocellular carcinoma, and human cervical cancer through the activating 3-kinase (PI3K)/Akt signaling pathway (8)(9)(10) . Meanwhile, activation of PI3K/Akt signaling has been reported to be beneficial in sepsis (11)(12)(13)(14)(15).…”
Section: Original Articlementioning
confidence: 99%